PENGARUH ION PENGGANGGU Pb2+ DAN Fe2+ TERHADAP ELEKTRODEPOSISI LOGAM KADMIUM (Cd) DALAM SAMPEL AIR - Miu, Agustinus; -, Alimuddin; Yusuf, Bohari (Jurusan Kimia FMIPA UNMUL, 2016)
The research was performed about interferes between of ion Pb2+ and Fe2+ on electrodeposition of ion Cadmium (Cd) in the water sample with electrode Al-Al. Electrolysis on solution 3CdSO4. 8H2O with three parameters, like time variation of electrolysis, influence variation of concentration Pb2+ ions and influence of mix variation concentration of ions Pb2+ and Fe2+. The results showed that the longer electrolysis, more metal deposition on the electrode. Based on observation, variation the number level of metals Cadmium (Cd) that deposition on the electrode was up 83.62 % on 120 minutes. The variations of addition of ion Pb2+ (2, 4, 6, 8 and 10 mg/L) obtained percent decrease in the level of disruption to in a solution of ion Cadmium (Cd) with average 21.53 % with every addition concentration of disruptor ion Pb2+ give influence 0.21 %. The variations of the addition disruptor ion Pb2+ and Fe2+ (2, 4, 6, 8 and 10 mg/L) obtained percent decrease of disruption in solution of ion Cadmium (Cd) with result 18.46 %, with each addition of ion Pb2+ and Fe2+ obtained 0.96 %. This showed that the addition of the ion disruptor on proccess electrodeposition given influence on Cadmium (Cd) electrodeposition itself, but for every addition of concentration given less significant effects. Keywords: Electrodeposition, electrode Al-Al and decrease percentace.